Cross-Linguistic Investigation of Projection in Overlapping Agreements to Assertions: Stance-Taking as a Resource for Projection. Issue 4 (21st April 2021) - Vatanen, Anna; Endo, Tomoko; Yokomori, Daisuke
Abstract: The human ability to anticipate upcoming behavior not only enables smooth turn transitions but also makes early responses possible, as respondents use a variety of cues that provide for early projection of the type of action that is being performed. This article examines resources for projection in interaction in three unrelated languages—Finnish, Japanese, and Mandarin—in sequences where speakers make evaluative assertions on a topic. The focus is on independently agreeing responses initiated in early overlap. Our cross-linguistic analysis reveals that while projection based on the ongoing turn-constructional unit relies on language-specific grammatical constructions, projection based on the larger context seems to be less language-dependent. A crucial finding is that in the target sequences, stances taken toward the topic already during earlier talk, as well as other structural patterns, are among the resources that recipients use for projecting how and when the ongoing turn will end.